Assessment of mineral contents in aerial parts of Schizachyrium microstachyum (Poaceae) - Villafañe, Roxana Noelia (2013)
This work describes the determination and evaluation of the mineral composition (Ca. Mg, Fe, Mn and Zn) of aerial parts of Schizachyrium microstachyum grown in two soil series within the Corrientes province, Argentina. This species is part of natural grassland used for extensively livestock production. The sampling process was performed during the summer and winter. Organic matter was eliminated by using dry-ashing digestion. Analyses were performed by inductively coupled plasma optical emission spectrometry (ICP-OES). Principal component analysis (PCA) and hierarchical cluster analysis (HCA) revealed different mineral compositions of the samples collected from the different kind of soils. Samples collected in the Chavarria´s series showed higher concentrations of micronutrients (Fe, Mn and Zn) and macronutrients (Ca and Mg). The average contents (µg per 100 g d.w.) of samples collected from Chavarria and Pampin series were 750 and 735 for calcium; 217 and 186 for magnesium; 38.1 and 44.3 for iron; 13.3 and 12.9 for zinc and 110.8 and 84.0 for manganese, respectively. Our results revealed that the studied forage were poor in the contents of the 5 measured essential elements (from the nutritional quality point of view). These results suggest the need for mineral supplementation for livestock production.